2018
DOI: 10.1111/eve.13008
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of blackthorn injury and synovitis in 35 horses

Abstract: SummaryThe objective of this prospective clinical study was to investigate the cause and describe the presentation, diagnosis, treatment techniques and outcome of Prunus spinosa (blackthorn) injury and synovitis in the horse. In all cases presented with blackthorn injury and synovitis, surgical treatment was performed within 24 h, using a two‐stage procedure: 1‐Perisynovial technique using ultrasound guided electrosurgical dissection; 2‐Endoscopic technique. The diagnosis was confirmed by retrieval of black pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…All six studies had small numbers of horses (range 3‐16), and no statistical analysis was performed on outcome for any of the studies. One study specifically described treatment for horses with blackthorn synovitis, 47 and one study identified outcomes in working equids 48…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All six studies had small numbers of horses (range 3‐16), and no statistical analysis was performed on outcome for any of the studies. One study specifically described treatment for horses with blackthorn synovitis, 47 and one study identified outcomes in working equids 48…”
Section: Resultsmentioning
confidence: 99%
“…One study specifically described treatment for horses with blackthorn synovitis, 47 and one study identified outcomes in working equids. 48…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…A range of synovial fluid analysis inclusion criteria are demonstrated in the above studies, and it would be important to use standardised diagnostic values for synovial sepsis in future studies. It is important to also be aware that the synovial fluid analysis values can vary, depending on the nature and duration of the underlying injury causing sepsis; for example, the synovial fluid TNCC can be significantly higher if the injury is caused by Prunus spinosa (blackthorn) (Ashton, 2018). It is beyond the scope of this article, however, it would be valuable in future studies to evaluate the financial implications of the different treatment methods, to further assess the effects of specific synovial fluid analysis results on the prognosis and to document the long‐term outcome of synovial sepsis affecting different synovial cavities.…”
Section: Discussionmentioning
confidence: 99%
“…The causes include traumatic injury, wounds (Milner et al., 2014), foreign body penetration (e.g. organic material such as blackthorn [Ashton, 2018]), iatrogenic causes (Lapointe et al., 1992) and haematogenous spread, the latter more commonly seen in neonates (Crosby et al., 2019; Lindegaard et al., 2021). Synovial sepsis is a serious, potentially life‐threatening and performance‐limiting condition (Richardson & Stewart, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, only a small number of studies use multivariable analysis to investigate factors associated with short‐term and long‐term survival after treatment and the factors that have been identified differ between studies and lack consistency 10 . There are only a small number of studies that involve multiple centers 7,11 or use a prospective study design 12 …”
Section: Introductionmentioning
confidence: 99%